A Social Learning Analysis Study: Social Presence in Online Discussions’ Network Interactions - Harati, Hoda; Tu, Chih-Hsiung; Yen, Cherng-Jyh; Liu, Yingying; Nasr, Nesma Raghab; Werner, Jennifer (Journal of educational technology development and exchange, 2025)
The significance of social presence is pivotal for online students’ participation in online discussion boards. Yet, it remained ambiguous how students evolved their social presence in their network interaction development. This research delved into the extent to which social presence moderated trends over time in several facets of students' prominence within social learning analysis of online discussions. The social network analysis (SNA) employed revealed that students’ prominence, including betweenness centrality, closeness centrality, eigenvector centrality, and PageRank, showed no notable growth over the duration of a 7-week online course. Moreover, the consistent trend observed in betweenness, eigenvector, and PageRank, coupled with the declining trend in closeness, was consistent across participants, irrespective of their level of social presence. These findings underscored the high interactivity of the students over time, offering valuable guidance for online educators and instructors to effectively sustain students' social presence and interconnectivity in online discussion boards effectively and continuously.